The Initial Prosecution of Miner's Fund - BENHAFED, Bibia (Journal of Human Sciences, 2020)
The initial jurisdiction over funds of the juvenile, is intended to preserve it interest..All the provisions enunciated by the positive law deriving from Islamic jurisprudence are intended to protect the funds of the minor.Establishing as a whole guaranties .islamique jurisprudence stipulated that the mandateshould be given to the father’s initial and then to the grandfather. While the Algerian legislator confide the mandate to the mother in the absence of the father then the grandfather and the gardien.. All these provisions agreed that certains conditions should exist in the agent, who is obliged to take care, preserve the funds of the minor, and have limited his powers by order of the judge and others without restrictions. In case of infraction, he is responsible . .the judge can also dimisss the guardian if it is proven that he is acting in a way that threatens the interests of the minor.